2021
DOI: 10.1080/14693062.2021.1948384
|View full text |Cite
|
Sign up to set email alerts
|

Caught in between: credibility and feasibility of the voluntary carbon market post-2020

Abstract: On the one hand, a large number of companies have committed to achieve net zero emissions and many of them foresee to offset some remaining emissions with carbon credits, suggesting a surge of future demand. Yet, the supply side of the voluntary carbon market is struggling to align its business model with the new legal architecture of the Paris Agreement. This article juxtaposes these two perspectives. It provides an overview of the plans of 482 major companies with some form of neutrality/net zero pledge and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
78
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 20 publications
0
78
0
Order By: Relevance
“…Hasenheit et al (2016) highlighted the importance of ensuring broad cooperation between decision makers, scientists, policy makers, and NGOs when developing new biorefining technologies to ensure socio-economic benefits are inclusive and sustainable. With proper policy direction and cooperation between the aforementioned communities, CDR has the potential to enhance the socio-economic impact of biorefining technologies through increased revenue and enhanced job security, particularly to rural areas ("Buy Clean California Act," 2017; Kreibich and Hermwille, 2021;Schenuit et al, 2021). Current and emerging financial incentives for CDR are beginning to have positive effects on various bioeconomies around the world.…”
Section: Circularity In Food and Agricultural Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hasenheit et al (2016) highlighted the importance of ensuring broad cooperation between decision makers, scientists, policy makers, and NGOs when developing new biorefining technologies to ensure socio-economic benefits are inclusive and sustainable. With proper policy direction and cooperation between the aforementioned communities, CDR has the potential to enhance the socio-economic impact of biorefining technologies through increased revenue and enhanced job security, particularly to rural areas ("Buy Clean California Act," 2017; Kreibich and Hermwille, 2021;Schenuit et al, 2021). Current and emerging financial incentives for CDR are beginning to have positive effects on various bioeconomies around the world.…”
Section: Circularity In Food and Agricultural Systemsmentioning
confidence: 99%
“…In the US, the low carbon fuel standard (LCFS) and 45Q carbon oxide tax credit are two policy-driven incentives for capturing and sequestering biogenic CO 2 ("Buy Clean California Act," 2017; Internal Revenue Service (IRS) and Treasury Department, 2021; Schenuit et al, 2021). In addition, voluntary, policy-agnostic markets for trading carbon credits are developing rapidly and have the potential to positively impact stakeholders throughout the bioeconomy (Kreibich and Hermwille, 2021). However, the credibility and feasibility of voluntary carbon markets vary widely, thereby warranting caution to any stakeholder interested in participating.…”
Section: Circularity In Food and Agricultural Systemsmentioning
confidence: 99%
“…Indeed, some of those working on corporate pledges -including sustainability experts -have concluded that their (Type 2) organisational missions render them poorly placed to adopt policies in line with Type 4 climate and biodiversity crises (Fancy, 2021;Kishan, 2021). This may be why less attention has been placed on this history of failed pledges in the past and, instead, on the opportunity to advance Type 4 problems by designing Type 2 policies tools in ways that might create synergies with Type 4 problems (Bos and Wu;Kreibich and Hermwille, 2021). It is for these reasons that many companies have expressed concerns that while they have made pledges on deforestation and climate, they are not fully aware of what this means in practice and what they might do to foster such a process.…”
Section: Net Zero and No Deforestation Pledgesmentioning
confidence: 99%
“…The carbon offsetting market is rapidly increasing and expected to grow by a factor of 100 until 2050 due to high demand and available capital (Blaufelder et al 2021). However, the main obstacle is limited supply of offsetting projects as forest owners lack upfront capital and market access (Kreibich and Hermwille 2021).…”
Section: Introductionmentioning
confidence: 99%